PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KECERDASAN MORAL SISWA KELAS VIII.6 SMP TRI BHAKTI PEKANBARU T.P 2014/2015 - Christy nanda pamungkas nanda pamungkas; Elni Yakub Elni Yakub; Zulfan Saam Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Our condition of education today,we fell that the student s are having crisis of moral intelligence,in the field,we can find students do not behave politely, both to friends or to the teacher. 1) To know the students moral intellegence bifore group counseling services given. 2) To know the process of implementation of group counseling services to ward students moral intellegence. 3) To determine the increase of moral intellegence of students after a given group counseling services. 4) to identify differentiation before and after students’ morall intellegence of group counseling Service has applied. 5) to identify the effect of group counseling service on student’ moral intellegence. This research used a pre-experimental design with one group pretest-posttest design. The subject of this research were the of VIII.6 class student SMP Tri Bhakti Pekanbaru, academic year 2014/2015 consist of 30 students. To take the sampling used saturated sample was used to determine the 30 samples. To distinguish the student’ moral intellegence before and after implementing information service using